Two minutes over Baghdad - Perlmutter, Amos.; Handel, Michael I.; Bar-Joseph, Uri. (London ; Portland, OR : Frank Cass, 2003)
A detailed account of the way Israel dealt with the Iraqi nuclear buildup between its launch in 1974 and the destruction of the Tamuz I reactor on 7 June 1981. This updated account includes formerly classified information and photographs taken during the mission and from US spy satellites.
Part PART ONE THE CALL TO ARMS AND THE NUCLEAR RACE -- chapter 1 Ben Gurion's Dilemma -- chapter 2 The Lion and the Lambs: The Birth of Israel's Nuclear Debate -- chapter 3 Nasser's Nightmare, Sadat's Solution -- chapter 4 The Quest for the Muslim Bomb: Libya, Syria, Saudi Arabia and Pakistan -- chapter 5 A Bomb in the Basement: Dayan's Formula -- chapter 6 Saddam Hussein and Project Tammuz -- part PART TWO THE DECISION IS MADE -- chapter 7 The Writing on the Wall: Sabotage in France -- chapter 8 The Writing on the Wall: Tearing the Thread -- chapter 9 Final Warning: The Iranian Attack -- chapter 10 The Trio Decide -- part PART THREE THE PREPARATIONS FOR OPERATION BABYLON -- chapter 11 Operation Babylon: Options -- chapter 12 Operation Babylon: A Second Entebbe? -- chapter 13 Operation Babylon: Reconnaissance -- chapter 14 Operation Babylon: The Eagle and the Fighting Falcon -- chapter 15 Operation Babylon: The Approach Route -- chapter 16 Operation Babylon: A Choice of Weapons -- chapter 17 Operation Babylon: Countdown -- chapter 18 Operation Babylon: Two Minutes over Osirak -- part PART FOUR JUDGMENT -- chapter 19 The Jerusalem Statement -- chapter 20 The Baghdad Statement -- chapter 21 Dropping Bombs and Clangers: Israel after the Raid -- chapter 22 The Propaganda War: Hussein Hits Backs -- chapter 23 A Delicate Balancing Act: The American Reaction -- chapter 24 Israel's Verdict -- chapter 25 The French Disconnection -- chapter 26 The Arab World: Bridging the Nuclear Gap -- chapter Epilogue to the Second Edition.
Print version record.
eBooks on EBSCOhost
Keywords: Arab-Israeli conflict; Baghdad (Iraq) -- History -- Bombardment, 1981.; Conflit israélo-arabe.; HISTORY -- General; Arab-Israeli conflict; Iraq -- Baghdad; 1981; Electronic books; History